ENHANCING EXPORT PERFORMANCE OF COASTAL SEAFOOD SMEs THROUGH COLLABORATIVE NETWORKS IN SIDOARJO, INDONESIA - Soleh Hanafi Ihsan Ihsan; Sudarmiatin; Heri Pratikto (PT. Habe Cendekia Utama, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a critical role in Indonesia’s economy, particularly in the seafood processing sector. However, these enterprises face significant challenges, including limited access to financing, global market networks, and competitiveness against larger firms. This study explores the socio-economic collaboration between seafood processing MSMEs in Sidoarjo and local stakeholders, including fishers, cooperatives, non-governmental organizations (NGOs), and village governments, in enhancing export performance. Using a qualitative descriptive approach through in-depth interviews and participatory observations, the findings indicate that sustainable and trust-based relationships between MSMEs and fishers are crucial for ensuring high-quality raw materials and competitive products in international markets. Collaboration with NGOs and cooperatives provides capacity-building, training, and improved access to financial resources. Village government support facilitates access to assistance programs, training, and product certification for export purposes. These results suggest that multi-stakeholder collaboration can overcome MSME challenges, expand export opportunities, and strengthen the global competitiveness of processed seafood products. The study offers practical insights for policy interventions aimed at supporting MSME development and international market expansion in the seafood sector.